2019
DOI: 10.1073/pnas.1903991116
|View full text |Cite
|
Sign up to set email alerts
|

Kinome profiling of non-Hodgkin lymphoma identifies Tyro3 as a therapeutic target in primary effusion lymphoma

Abstract: Non-Hodgkin lymphomas (NHLs) make up the majority of lymphoma diagnoses and represent a very diverse set of malignancies. We sought to identify kinases uniquely up-regulated in different NHL subtypes. Using multiplexed inhibitor bead-mass spectrometry (MIB/MS), we found Tyro3 was uniquely up-regulated and important for cell survival in primary effusion lymphoma (PEL), which is a viral lymphoma infected with Kaposi’s sarcoma-associated herpesvirus (KSHV). Tyro3 was also highly expressed in PEL cell lines as wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 75 publications
0
16
0
Order By: Relevance
“…CRISPRi had no effects on the expression of neighboring genes ( Supplementary Fig. 5a, b) SEs were also present in CFLAR TSS/first intron, TYRO3 loci in all or some PEL cell lines 60 , and long non-coding RNAs, such as NEAT1 and MALAT1 ( Supplementary Fig. 6).…”
Section: Relative Luminiscencementioning
confidence: 99%
“…CRISPRi had no effects on the expression of neighboring genes ( Supplementary Fig. 5a, b) SEs were also present in CFLAR TSS/first intron, TYRO3 loci in all or some PEL cell lines 60 , and long non-coding RNAs, such as NEAT1 and MALAT1 ( Supplementary Fig. 6).…”
Section: Relative Luminiscencementioning
confidence: 99%
“…TRex-RTA BCBL-1 cells were intraperitoneally (i.p.) injected into NSG mice, allowing us to visualize the tumor growth upon injection of luciferin (25,32). After four weeks of treatment, the combination of miransertib and sirolimus significantly reduced growth compared to the vehicle (Figures 6C, D).…”
Section: Miransertib Synergizes With Sirolimus To Reduce Tumor Growth In a Pel Xenograft Modelmentioning
confidence: 99%
“…Solid tumors were fixed in 10% formalin vials (Fisher Scientific) for up to 3 days, and sections were processed as previously (25). The pS6 primary antibody was purchased from CST (4858) and used at a dilution of 1:400.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…Subsequently, a study by Mohanty et al [ 320 ] revealed everolimus as a multi-targeted therapy that induces apoptosis and downregulates mTOR, STAT-3 and NF-κB signaling in KSHV+ PEL [ 320 ]. Recent kinome profiling of PEL cell lines using kinase inhibitor-conjugated beads to capture kinases followed by quantitative MS revealed Tyro3 as a potential therapeutic target with subsequent analyses revealing that Tyro3 inhibition reduced PEL survival and growth in vitro, and tumor burden in a mouse PEL xenograft model in vivo [ 321 ]. KSHV latency-associated nuclear antigen (LANA) was found to prevent degradation of the oncogene c-Myc in PEL cell lines by inhibiting glycogen synthase kinase-3β (GSK-3β)-mediated phosphorylation of the T58 residue of c-Myc [ 322 ].…”
Section: Lymphomasmentioning
confidence: 99%